Screening Approaches for Targeting Ribonucleoprotein Complexes: A New Dimension for Drug Discovery. (March 2019) - D'Agostino, Vito Giuseppe; Sighel, Denise; Zucal, Chiara; Bonomo, Isabelle; Micaelli, Mariachiara; Lolli, Graziano; Provenzani, Alessandro; Quattrone, Alessandro; Adami, Valentina
RNA-binding proteins (RBPs) are pleiotropic factors that control the processing and functional compartmentalization of transcripts by binding primarily to mRNA untranslated regions (UTRs). The competitive and/or cooperative interplay between RBPs and an array of coding and noncoding RNAs (ncRNAs) determines the posttranscriptional control of gene expression, influencing protein production. Recently, a variety of well-recognized and noncanonical RBP domains have been revealed by modern system-wide analyses, underlying an evolving classification of ribonucleoproteins (RNPs) and their importance in governing physiological RNA metabolism. The possibility of targeting selected RNA–protein interactions with small molecules is now expanding the concept of protein "druggability, " with new implications for medicinal chemistry and for a deeper characterization of the mechanism of action of bioactive compounds. Here, taking SF3B1, HuR, LIN28, and Musashi proteins as paradigmatic case studies, we review the strategies applied for targeting RBPs, with emphasis on the technological advancements to study protein–RNA interactions and on the requirements of appropriate validation strategies to parallel high-throughput screening (HTS) efforts.